Prevalence of Hiv Infection Among Pregnant Women Attending Ajiko Medical Clinic, Damaturu, Nigeria - Sabina, Khanam (Journal of Clinical Research In HIV AIDS And Prevention, 2019)
Human immunodeficiency viruses causes HIV infection in humans belongs to two species of Lentivirus. It damages the cells of immune system which leads to weak immune system and the ability to fight from infections and diseases. This study was conducted to investigate the prevalence rate of HIV infection among pregnant women of different age groups attending Ajiko medical clinic, Damaturu, Nigeria. The prevalence rate was maximum (12.5%) in 36-45 age group and minimum (5%) in 26-35 age group but their was no HIV infection in 15-25 age group. The overall prevalence rate among pregnant women was 4%. General knowledge , training and campaigns of HIV prevention need to be tailored towards older women of age group 36-45 because of high prevalence rate.